Effect of single dose dexamethasone (0.1 mg/kg) on white blood cell counts and serum glucose levels in healthy ewes - Orhan Corum; Burak Dik; Ayse Er (Eurasian Journal of Veterinary Sciences)
Aim: Aim of this research was to determine that effect of single dose dexamethasone (0.1 mg/kg, SC) on the white blood cell counts and serum glucose levels in healthy ewes. In addition, effects of dexamethasone on the other hemogram and serum biochemical values were evaluated. Materials and Methods: Totally healthy 8 Akkaraman sheep were received with 0.1 mg/kg (SC, single dose) dexamethasone. Blood samples were taken before (0. hour, control) and after treatments at 4, 8, 12, 24, 36, 48 and 72 hours. White blood cell, red blood cell, platelet, hematocrit and hemoglobin levels were measured by hemocell counter, whereas serum glucose, lactate dehydrogenase, alkaline phosphatase, total bilirubin, alanine aminotransferase, aspartate aminotransferase, gamma glutamyltransferase, total protein, albumin, blood urea nitrogen, creatinine, cholesterol, triglyceride, high density lipoprotein and low density lipoprotein levels were determined by auto-analyzer. Results: Dexamethasone increased (P<0.05) white blood cell and glucose levels when compared to Control (0 hour), and higher levels of these values were monitored during 48 hours. In addition, statistically significance changes were determined in the total bilirubin, triglyceride and blood urea nitrogen concentrations, but these results were within reference range. Conclusion: It may be stated that dexamethasone increases white blood cell count and glucose levels in sheep and its effect may be determined during 2-3 days after treatments.